Synthetic Cannabinoid AB-FUBINACA Negatively Impacted the Male Fertility and Induced Testicular Toxicity - Ayman Alzu’bi (13162392) (2025)
Purpose The recreational use of synthetic cannabinoids (SCs) by adolescents and adults has markedly increased in recent years. Previous studies demonstrated that exposure to SCs is associated with multiple adverse health effects. Nevertheless, little is known about the effects of these substances on male fertility. The current study aimed to investigate the toxicological effects of subacute exposure to synthetic cannabinoid AB-FUBINACA on male reproductive system in mice. Methods Adult male Balb/c mice received daily intraperitoneal injections of various doses of AB-FUBINACA (0.75, 1.5, and 3 mg/kg for 3 weeks). Using biochemical and molecular methodologies, the impact of AB-FUBINACA on serum levels of reproductive hormones, sperm viability as well as various parameters in testicular tissue were evaluated. Results Our findings demonstrated that AB-FUBINACA induces dose-dependent reduction in testosterone levels in the serum, but not in follicle-stimulating hormone or luteinizing hormone. AB-FUBINACA treatment also causes a significant dose related decrease in sperm viability. These findings were associated with higher level of oxidative stress (GP91 expression and malondialdehyde level) and elevated expression of key regulators of apoptosis (Bax and caspase-3) as well as reduced expression of mitochondrial respiratory chain complexes SDHB (II), UQCRC2 (III), and ATP5a (V) in the testicular tissue. Conclusion From these findings, it can be concluded that exposure to AB-FUBINACA can interfere with the normal physiology and functioning of the male reproductive organs. Hence, gaining insight into the mechanisms by which SCs interfere with male fertility could guide future interventions and treatments. Other Information Published in: Forensic Toxicology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11419-025-00739-y